(untitled) (Research, Society and Development, 2021)
Introduction: Pregnancy and puerperium present countless transformations in women’s lives. In this sense, health education actions are essential for the prevention of injuries, diseases and complications. Objective: To analyze the actions of health education developed in primary care for the prevention of diseases and improvement of quality of life in pregnancy-puerperium cycle. Method: Integrative literature review from the Scientific Electronic Library Online and Latin American and Caribbean Literature on Health Sciences, Nursing Database and U. S. National Library of Medicine databases, from 2016 to 2021. The following Health Sciences Descriptors and their combinations in Portuguese and English were used: "health education" AND "primary care" AND "pregnant women"; "health education" and "primary care" and "pregnancy". The final sample consisted of 20 articles. Results: It was found that the period of greatest approach was during pregnancy, with 75% of the articles. Finally, 75% of the articles studied were related to educational practices, of which dialogue was the most prominent, with 25%. However, educational workshops also stood out with 20%. Conclusion: It is notorious the importance of the approach to health education in primary care for the qualification of the health of pregnant and postpartum women attributed to the prevention of injuries, diseases and complications in this period. Thus, it highlights the need for continuity, intensification and expansion of educational strategies in health developed in primary care as a fundamental tool in the gravidic-puerperal cycle.